Evaluating Public Health Interventions: A Neglected Area in Health Technology Assessment - Stojanovic, Jovana; Wübbeler, Markus; Geis, Sebastian; Reviriego, Eva; Gutiérrez-Ibarluzea, Iñaki; Lenoir-Wijnkoop, Irene (Frontiers in Public Health, 2020)
Introduction: Public health (PH) interventions are crucial for ensuring sustainable healthcare services. Nevertheless, they represent a neglected area in the field of health technology assessment (HTA) due to various methodological issues and their complex design that goes beyond clinical setting. The present study provides an environmental scan of HTA initiatives related to the assessment of PH technologies on a global level. Methods: We conducted a cross-sectional survey among 85 HTA-related European and international societies, health bodies, and networks from September 2018 to January 2019. The questionnaire contained four sections and 18 questions regarding activities related to the evaluation of PH technologies, information on existing PH technologies, and methodologies of assessment as well as barriers and facilitators to reaching a decision and implementing a PH technology. Results: Among 52 survey responses, the majority of the respondents came from European countries (35%), followed by North American (27%), and South American (19%) countries. The main type of organizations covered by our survey included HTA agencies, public administrations, and research institutes. Seventy-one % of the institutions reported engagement in any aspect of HTA in the area of PH (N = 37). Among those, 81% evaluated less than 5 PH technologies from 2013 to 2018. The most common barriers for reaching a decision on PH technologies were lack of data, conflicting stakeholder priorities, and methodological issues. A total of 76 PH interventions were reported, and most cited initiatives were related to chronic disease screening, prevention of infectious diseases, and maternal, prenatal, and neonatal screening. Conclusion: Our survey reported a rather limited involvement of HTA in the evaluation of PH technologies. In particular, an evaluation of behavioral and lifestyle interventions remains extremely rare. The implementation of collaborative HTA approaches in the setting of PH practice and policy needs to be prioritized and further strengthened. Moreover, ensuring reliable data structures and consolidation of HTA methods for the evaluation of PH technologies will be crucial for tackling the enormous burden of non-communicable diseases in societies.